Prevalence of Dysmenorrhea and Its Effect on the Quality of a Female's Life - Bilal Ahmad; Sumia Fatima; Warda Fatima Shafee; Mahnoor Asghar Keen; Marwa Mehak; Manahil Noor; Abdul Majid; Shayan Ali Khan (Fakultas Kesehatan Masyarakat Universitas Muslim Indonesia, 2026)
Dysmenorrhea, a common gynecological complaint among young females, manifested with severe pain in 36.6% (117/320) of participants and moderate-to-severe quality of life (QoL) impairment in 74.2% (222/320) among female medical students in Khyber Pakhtunkhwa, Pakistan. This cross-sectional study utilized non-random convenience sampling to enroll 320 participants, who completed a reliable self-structured questionnaire (Cronbach's α = 0.72). Associations between dysmenorrhea factors and QoL domains (mild, moderate, severe) were evaluated using Pearson chi-square tests. No significant association was observed between menstrual pain intensity and QoL (χ2=25.932, df = 20, p = 0.168). In contrast, breakfast skipping showed a strong association with QoL (χ2=12.958, df = 2, p = 0.002). Associated symptoms (χ2=24.289, df = 10, p = 0.007) and irregular menstrual cycles (χ2=7.429, df = 2, p = 0.024) also demonstrated significant links, highlighting lifestyle and symptom clustering effects. These findings underscore that QoL burdens stem primarily from modifiable factors beyond pain severity alone. Targeted non-pharmacological interventions—such as nutritional education to encourage breakfast consumption and proactive symptom management—are recommended to mitigate dysmenorrhea's impact and enhance well-being in this population.